Analisis soal HOTS pada Buku Studio Express A1 - Karim, Ella Mei Laila; Perdamean, Ahmad Sahat (VISA: Journal of Vision and Ideas, 2024)
The aim of this research is to find out how the questions are distributed in the Studio Express A1 book with the topic "Deutsch im Kurs" and the results of the analysis of the questions in the Studio Express A1 book with the topic "Deutsch im Kurs" based on cognitive level. This research was conducted in the library of the Faculty of Languages and Arts, Medan State University. In this research, a qualitative descriptive method was used. The data source is taken from the Studio Express A1 book. The data used in this research are German language topic questions in the course. The theory used in this research is Bloom's taxonomy revised by Anderson and Krathwohl. For data analysis, the Milesund Huberman technique was used, namely data collection, data reduction, data presentation and conclusions. The topic "Deutsch im Kurs" consists of 46 questions. The results of research questions on the topic "Deutsch im Kurs" are LOTS (Low Order Thinking Skills) with a total of 31 questions = 67.3%, MOTS (Middle Order Thinking Skills) with a total of 8 questions = 17.2% and HOTS (High Order Thinking Skills) with a total of 7 questions = 15.2%. This shows that these questions are not yet included in the HOTS questions, because the analysis results show that the HOTS category is lower than the MOTS category with an overall percentage of 17.2%, while HOTS is only 15.2%.